ChemInform Abstract: Microwave‐Assisted One‐Pot Synthesis of Bioactive Ugi‐4CR Using Fluorite as Benign and Heterogeneous Catalyst. Issue 9 (4th March 2014) - Mohanram, Ipsita; Meshram, Jyotsna; Shaikh, Ambareen; Kandpal, Bhavna
Abstract Ugi derivatives (V) are synthesized and screened for their potential antibacterial activities.